Oxidative stress and antioxidants in athletes undertaking regular exercise training - Watson, T. A.; MacDonald-Wicks, L. K.; Garg, M. L. (International Journal of Sport Nutrition and Exercise Metabolism, 2005)
Exercise has been shown to increase the production of reactive oxygen species to a point that can exceed antioxidant defenses to cause oxidative stress. Dietary intake of antioxidants, physical activity levels, various antioxidants and oxidative stress markers were examined in 20 exercise-trained "athletes" and 20 age- and sex-matched sedentary "controls." Plasma F2-isoprostanes, antioxidant enzyme activities, and uric acid levels were similar in athletes and sedentary controls. Plasma alpha-tocopherol and beta-carotene were higher in athletes compared with sedentary controls. Total antioxidant capacity tended to be lower in athletes, with a significant difference between male athletes and male controls. Dietary intakes of antioxidants were also similar between groups and well above recommended dietary intakes for Australians. These findings suggest that athletes who consume a diet rich in antioxidants have elevated plasma alpha-tocopherol and beta-carotene that were likely to be brought about by adaptive processes resulting from regular exercise.